Investigation of ternary blends of animal fat biodiesel-diethyl ether-diesel fuel on CMFIS-CI engine characteristics. (15th January 2023) - Ashfaque Ahmed, S.; Elahi M. Soudagar, Manzoore; Rahamathullah, I.; Sadhik Basha, J.; Yunus Khan, T.M.; Javed, Syed; Elfasakhany, Ashraf; Kalam, MA
Graphical abstract: Highlights: Animal fat biodiesel (AFB) was synthesized using transesterification reaction, 90% AFB yield was obtained. Ternary blends AF (B20)-neat diesel (ND)-diethyl ether (DEE) were utilized, DEE is varied 10% and 20%. For AFB20DEE20, BTE enhances by 5.8% and reduces BSFC by 6.89% and increases BSEC by 1.93% compared with ND. For AFB20DEE20, Lower EGT, reduction in CO and UHC by 37.8% and 50.7% compared to ND. Smoke lowered by 41.07% and NOx slightly increased for AFB20DEE20 compared to AFB20. Abstract: The experimental study aims at investigation of the ternary blends of animal fat oil biodiesel, diesel and diethyl ether in-terms of performance, emission and combustion analysis in single cylinder four stroke diesel engine. The animal (mono) fat biodiesel was prepared through transesterification process by using alcohol (6:1) and potassium hydroxide (4:1) at 50 °C –55 °C and obtained 90 % of biodiesel. The prepared biodiesel was blended with neat diesel to get the tested blend, animal fat biodiesel (AFB20). To improve the performance parameters of AFB20, the prepared biodiesel blend AFB20 was again blend with diethyl ether (DEE) in various proportions by 10 % and 20 % to obtain the ternary blend AFB20DEE10 and AFB20DEE20. Addition of DEE to AFB20 enhances the physicochemical properties of the biodiesel blends. The first stage of this study was that the neat diesel was examined in the single cylinder four stroke diesel engine to obtain the reference readings. The second and third stage of this investigation was the prepared animal fat biodiesel blend AFB20 and AFB20DEE10 and AFB20DEE20 were examined in the diesel engine. The fourth stage of this investigation was that, the obtained results of neat diesel was compared with the other tested blends. The experimental outcome reveals that, AFB20DEE20 blend perform better than that of the other tested blends. 4.8 % higher fuel is consumed, and 7.1 % lowered brake thermal efficiency and exhaust gas temperature was found in the blend AFB20DEE20 compared to neat diesel. The blend AFB20DEE20 exhibits higher cylinder pressure by 70.43 bar and lower heat release rate by 35.23 J/deg., compared to neat diesel. 0.15 % lower CO emission and 37.8 % lower UBHC emission were found in AFB20DEE20 compared with ND. Reduction of NO x emission by 4.18 % and higher smoke emissions were found in the blend AFB20DEE20 compared to neat diesel.